2004
DOI: 10.1021/nl048774r
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Control of Room-Temperature Ionic Liquid Templated Mesoporous Silica Nanoparticles for Controlled Release of Antibacterial Agents

Abstract: A series of room-temperature ionic liquid (RTIL) containing mesoporous silica nanoparticle (MSN) materials with various particle morphologies, including spheres, ellipsoids, rods, and tubes, were synthesized. By changing the RTIL template, the pore morphology was tuned from the MCM-41 type of hexagonal mesopores to rotational moire ´type of helical channels, and to wormhole-like porous structures. These materials were used as controlled release delivery nanodevices to release antibacterial ionic liquids agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
287
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 416 publications
(293 citation statements)
references
References 18 publications
(16 reference statements)
5
287
0
1
Order By: Relevance
“…[1][2][3][4] Furthermore, recent reports on the design of functional mesoporous silica materials by decorating the pore surface with organic or inorganic moieties that could serve as gating devices to regulate the release of guest molecules under the control of several different external stimuli, such as chemicals, [5][6][7][8][9] temperature, 10 redox reactions, 11,12 and photoirradiation, 13,14 have highlighted the potential of utilizing this kind of nanodevice for many controlled release applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Furthermore, recent reports on the design of functional mesoporous silica materials by decorating the pore surface with organic or inorganic moieties that could serve as gating devices to regulate the release of guest molecules under the control of several different external stimuli, such as chemicals, [5][6][7][8][9] temperature, 10 redox reactions, 11,12 and photoirradiation, 13,14 have highlighted the potential of utilizing this kind of nanodevice for many controlled release applications.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have demonstrated that, by controlling the particle size, shape, and surface functionality of the mesoporous silicas, these structurally defined materials can be efficiently endocytosed by live cells with high biocompatibility in vitro and serve as delivery vehicles for the controlled release of genes and membrane-impermeable chemicals. 3,[5][6][7] Also, several enzymes have been shown to be functional without being denatured inside the frameworks of mesoporous silicas, such as MCM-41 and SBA-15 silicas. [15][16][17][18][19][20][21][22][23] However, to the best of our knowledge, there were only two prior reports on the controlled release of proteins from SBA-15-type mesoporous silica materials under nonphysiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…16 They have been successfully used to deliver drugs, 17,18 proteins 19 and nucleic acids. 20,21 Most recent efforts have been focused on their biological targeting in order to achieve site-specific delivery.…”
mentioning
confidence: 99%
“…Zhou et al and Zhang et al utilize 1-butyl-3-methylimidazolium tetrafluoroborate (C 4 MimBF 4 ) to synthesize mesoporous silica via a new mechanism, known as hydrogen bond-co-π-π-stack [1,32]. Despite these many researches conducted on usage of ILs as template, only one research was able to use ILs to develop MSNs and in this research, it was found that MSNs morphology are dependent on the type of ILs used [33].…”
Section: Introductionmentioning
confidence: 80%